1976
DOI: 10.1152/ajplegacy.1976.230.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemorrhagic shock on renal release of prostaglandin E

Abstract: The effect of hemorrhage and reinfusion on renal release of prostaglandin E (PGE), arterial [PGE], mixed-venous [PGE], and renal function was observed in anesthetized dogs. Following hemorrhage to 60 mmHg arterial pressure, arterial [PGE] rose significantly from 405 to 740 pg/ml. Renal release of PGE remained near control (8 ng/min), as renal blood flow (RBF) decreased from 4.7 to 2.2 ng/min per gram kidney weight (KW). Mixed-venous [PGE] remained near the control value (960 pg/ml). Reinfusion of shed blood re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…In previous studies, HH has been found to increase renal prostaglandin synthesis and release (14). Similarly, in the present study HH was found to increase renal medullary prostaglandin concentration.…”
Section: Resultssupporting
confidence: 88%
“…In previous studies, HH has been found to increase renal prostaglandin synthesis and release (14). Similarly, in the present study HH was found to increase renal medullary prostaglandin concentration.…”
Section: Resultssupporting
confidence: 88%
“…Support for this interpretation comes from the observation that PGE-like material in the renal vein of the dog is increased by hypoperfusion (25)(26)(27). Under these conditions in the dog, inhibition of cyclooxygenase markedly increases RVR (26)(27)(28).…”
Section: Discussionmentioning
confidence: 96%
“…In trauma patients, inhibitory activities affecting neutrophil chemotaxis, lymphocyte reactivity, and neutrophil chemiluminescence have been identified in the sera. [39][40][41][42] The nature of the inhibitory activity in trauma patients' sera is at present unknown. It is not clear whether it is a newly synthesized product, a protein, or a substance of a different nature.…”
Section: Discussionmentioning
confidence: 99%
“…This is a most powerful endogenous immune suppressant for T-cell and macrophage responsiveness. 26,42 Finally, PGE2 induces the release of the potent antiinflammatory cytokine IL-10, which has been found to contribute to endotoxin hyporesponsiveness in vitro, 43 and which is the functional suppressor in plasma patients with meningococcal sepsis. 44 Conversely, the use of IL-10 antibodies restored PGE2-induced monocyte suppression.…”
Section: Discussionmentioning
confidence: 99%